Psychological motives underlying selfie behavior among Egyptian college Students - Hanan Fawzy Aboelela Desokey (Northern Negros State College of Science and Technology (NONESCOST), 2021)
Selfie behavior is related to a set of motives that direct Egyptian college students to it; because this phenomenon reflects the behavior of these individuals. Therefore, the research aims to search behind the motives that cause this behavior and researched this phenomenon to identify what might drive college students participating in the research to photograph themselves and the extent of their difference that in terms of degree and gender. The number of participants in this study was 2,128 students from eight divergent colleges of Egyptian University. The results confirmed that five motives lie behind this, and they were arranged in a row, recording moments, communicating with others, being amused, supporting self-confidence, and seeking attention. The females differed from the males in the motives of amusement and attention-seeking where the differences were in favor of the females, and this was explained due to the different natures of life for both sexes in Egyptian society, where females have more free time, As for the rest of the motives, there were no differences between them, and they did not differ in the degree to which they took pictures in general, because this does not depend on gender as much as it depends on the availability of smart devices and their applications for them.